2013
DOI: 10.1007/s00415-013-6998-8
|View full text |Cite
|
Sign up to set email alerts
|

Widespread neuronal damage and cognitive dysfunction in spinocerebellar ataxia type 3

Abstract: Previous studies demonstrated cognitive impairments in spinocerebellar ataxia type 3 (SCA3/MJD); however, there is no consensus about the cognitive domains affected and the correlation with structural brain abnormalities. We investigated the neuropsychological profile and 3T-MRI findings, including high-resolution T1-images, diffusion tensor imaging and magnetic resonance spectroscopy of 32 patients with SCA3/MJD and 32 age-, gender- and educational level-matched healthy controls. We reviewed patients' clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
81
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 32 publications
4
81
0
Order By: Relevance
“…Pathological studies revealed severe neuronal loss predominantly in the cerebellum, brainstem, and basal ganglia [5]. This is indeed confirmed by recent quantitative neuroimaging data [6][7][8][9]. Damage to these regions accounts for the main clinical features in the disease, such as ataxia and movement disorders.…”
Section: Introductionmentioning
confidence: 66%
“…Pathological studies revealed severe neuronal loss predominantly in the cerebellum, brainstem, and basal ganglia [5]. This is indeed confirmed by recent quantitative neuroimaging data [6][7][8][9]. Damage to these regions accounts for the main clinical features in the disease, such as ataxia and movement disorders.…”
Section: Introductionmentioning
confidence: 66%
“…20 A single study evaluated the NAA ϩ N-acetyl-aspartylglutamate/total Cr ratio in the left cerebellar white matter of patients with SCA3/MJD and found reduced ratios. 26 Reduced NAA levels in the cerebellar vermis and pons, with a strong inverse correlation between SARA scores and NAA levels in the pons, were reported in a single study. 19 Two studies evaluated the NAA/ choline ratio 20,21 ; NAA/Cho ratio was reduced in the cerebellar vermis in both studies, but one reported a direct 20 and the other an inverse correlation 21 with SARA.…”
Section: Infratentorial Structuresmentioning
confidence: 82%
“…20 One study evaluated the glutamate (Glu)/total Cr ratio in the left cerebellar white matter and found reductions in SCA3/MJD, but with no correlations with motor clinical or molecular data. 26 One study evaluated MR spectroscopy Glu levels and found reductions in the cerebellar vermis and pons, with no significant clinical or molecular correlations.…”
Section: Infratentorial Structuresmentioning
confidence: 99%
See 2 more Smart Citations